Pendidikan tentang Pencegahan Penyakit Menular dan Penyakit Tidak Menular pada Masyarakat di Kabupaten Aceh Besar - Farrah Fahdhienie; Hidayati Savitri; Aryandi Darwis (Universitas Muhammadiyah Semarang, 2024)
The prevalence of morbidity and mortality due to communicable and non-communicable diseases continues to increase and is a major challenge for public health in the world and in Indonesia. The increase in these two types of disease shows that public awareness and knowledge regarding prevention still needs to be increased. Comprehensive and ongoing health education is the key to prevention efforts. Therefore, a community service program is needed that focuses on education on preventing communicable and non-communicable diseases in the community. This service activity uses an interactive educational method involving 25 participants (housewives and young women) in Teubang Phui Baro Village, Montasik District, Aceh Besar Regency. Pre-test and post-test measurements were carried out with a questionnaire consisting of eight questions to measure the increase in participants' knowledge. The results showed that all counseling participants experienced an increase in their knowledge scores after the counseling with an average increase in scores for this activity being 3.92 (range of score increase of at least 2 points and maximum 6 points). With the implementation of this outreach, it is hoped that the community will be able to change their behavior to be healthier in terms of consumption patterns, physical activity and other health behaviors.